From Regulation to Culture: Rethinking Global Anti-Corruption Law Enforcement - Dippo Alam; Maryano Maryano; Supaphorn Akkapin (CV. Era Digital Nusantara, 2025)
Corruption persists as one of the most entrenched challenges in global governance, undermining democratic institutions, economic development, and public trust. Despite the widespread adoption of international frameworks, such as the United Nations Convention against Corruption (UNCAC), and the proliferation of national anti-corruption agencies, empirical evidence suggests that regulatory instruments alone remain insufficient. Transparency International’s 2023 Corruption Perceptions Index reveals that two-thirds of countries score below 50 out of 100, reflecting limited progress despite extensive legal reforms. This study employs a qualitative-descriptive and comparative literature approach to analyze the limitations of formal regulation and to examine the role of legal culture in strengthening anti-corruption enforcement. Findings demonstrate that while regulatory frameworks provide essential normative foundations, sustainable compliance emerges only when integrity is embedded within societal values and norms. Comparative evidence from Singapore, Denmark, Finland, and Rwanda illustrates that internalized social trust, transparency, and accountability act as cultural multipliers of legal effectiveness. The study contributes to academic discourse by shifting the focus from purely legal and formal perspectives to the integration of socio-cultural dimensions, thereby addressing a significant research gap. Practically, it offers policy recommendations for embedding anti-corruption education, strengthening civil society, and fostering cultural transformation alongside legal reforms. Ultimately, effective global anti-corruption enforcement requires a paradigm shift—moving from regulation to culture.